Vanillin enhances the passive transport rate and absorption of drugs with moderate oral bioavailability in vitro and in vivo by affecting the membrane structure. Issue 1 (7th January 2020) - Huang, Wen'ge; Yang, Yingzhuo; Wen, Wen; Luo, Yu; Wu, Jiasi; Xiang, Li; Hu, Yinfan; Xu, Shijun; Chen, Simin; Wang, Ping
Abstract : Vanillin is a popular flavoring agent in the food, tobacco, and perfume industries. Abstract : Vanillin is a popular flavoring agent in the food, tobacco, and perfume industries. In this paper, we investigated the effect of vanillin on the transport rates of drugs with different levels of permeability (acyclovir, hydrochlorothiazide, propranolol and carbamazepine) through a Caco-2 cell bidirectional transport experiment. We also explored the underlying mechanism using an in silico technique and fluorescence anisotropy measurements. The influence of vanillin on the pharmacokinetics of drugs whose transport rates were affected by vanillin in vitro was then studied in vivo . Results showed that vanillin (100 μM) increased the cumulative amount of passively transported drugs (2.1-fold of hydrochlorothiazide, 1.49-fold of propranolol, 1.35-fold of acyclovir, and 1.34-fold of carbamazepine) in vitro . Molecular dynamics simulations revealed that vanillin disordered the structure of the lipid bilayer and reduced the energy barrier of drugs across the center of the membrane. The anisotropy of TMA-DPH also decreased in Caco-2 cells after treatment with vanillin (25 and 100 μM) and indicated an increase in membrane fluidity, which was dose-dependent. An oral bioavailability study indicated that vanillin (100 mg kg −1 ) significantly enhanced the C max and AUC0–6 of hydrochlorothiazide by 1.42-fold and 1.28-fold, respectively, and slightly elevated the C max of propranolol. In conclusion, vanillin can significantly increase the absorption of drugs with moderate oral bioavailability in vitro and in vivo by loosening the membrane. Thus, the concurrent consumption of drugs with food containing vanillin may result in increased drug plasma concentration and pose potential health risks.